1992
DOI: 10.1001/archsurg.1992.01420020028004
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 and Its Relationship to Endotoxin Tolerance

Abstract: Endotoxin (lipopolysaccharide [LPS])-induced cytokine release has been implicated in the pathogenesis of sepsis. Sublethal doses of LPS induce tolerance to a septic insult. This study evaluated pretreatment with interleukin 1 (IL-1) against an LPS challenge and examined its relationship to endotoxin tolerance. C3H/HeN mice (N = 100) were injected intraperitoneally with phosphate-buffered saline (control group), IL-1 (200 micrograms/kg), or LPS (1 mg/kg) for 3 days. On day 5, peritoneal macrophages were harvest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 37 publications
1
17
0
1
Order By: Relevance
“…Although other cytokines, such as IL-10 [9], TGF-b [9], IL-13 [8] and IL-1a [13], have also been involved in the mechanism of refractoriness to LPS, our results are probably only a partial expression of the complex phenomenon of endotoxin tolerance. However, we think that the study of mechanisms of IL-1b-induced tolerance leading to an anti-inflammatory activity deserve further investigation in the future.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Although other cytokines, such as IL-10 [9], TGF-b [9], IL-13 [8] and IL-1a [13], have also been involved in the mechanism of refractoriness to LPS, our results are probably only a partial expression of the complex phenomenon of endotoxin tolerance. However, we think that the study of mechanisms of IL-1b-induced tolerance leading to an anti-inflammatory activity deserve further investigation in the future.…”
Section: Discussionmentioning
confidence: 72%
“…Endotoxin desensitization has also been achieved in vitro with relative efficacy by individual cytokines, such as IL-10 [9] and transforming growth factor-b (TGF-b) [9], and in vivo by injection of IL-13 [8] and IL-1a [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, TNF-α expression remained elevated; therefore, a different mechanism for ET induction was suspected than in ET associated with low TNF-α expression (Leon et al 1992). …”
Section: Il-1mentioning
confidence: 63%
“…Potentially beneficial effects of IL-6 production during endotoxemia have been described and include decreased production of TNF-α and IL-6 by monocytes, and inducing production of the full range of acute-phase proteins, including protease inhibitors that are postulated to limit tissue damage (Robinson et al 1993). Other studies, however, have indicated that IL-6 may contribute to the pathogenic effects of gram negative infections or intravenous administration of TNF-α and that administration of IL-6 antagonists may be beneficial in endotoxemia (Leon et al 1992;Starnes et al 1990). LPS infusion in neonatal foals led to an increased production of IL-6 (Robinson et al 1993).…”
Section: Il-6mentioning
confidence: 99%
“…IL-1a appears in serum later than does TNFa, and is detectable after 1 hr, reaching its maximum levels between 2 and 3 hr [10]. IL-6 increases progressively and continuously, reaching its maximum value after 4 hr [11,12] (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%